CULTIVATING GOVERNMENT LAND FOR PERSONAL INTERESTS FROM ISLAMIC LAW AND POSITIVE LAW - Dhiauddin Tanjung (UNIVERSITAS PAKUAN, 2022)
One of the problems that is almost difficult to solve in Indonesia is the problem of land that is managed by both regional and central governments and then cultivated and used by the community individually and for personal interests not the interests of the general public. government land that is used for the welfare of the people for personal interests according to Islamic law and positive law, secondly how are the sanctions for cultivating the land for personal interests according to Islamic law and positive law. In this study the author uses a normative/doctrinal legal research method, namely discussing and reviewing the law contained in fiqh books or laws. Through this normative method, it can be seen that working on government land for the welfare of the people for personal interests is an act of land grabbing which can be categorized as an unlawful act and can be threatened with imprisonment for a maximum of 3 (three) months, or a fine of up to IDR 5,000. (five thousand rupiahs). Whereas in Islamic law that working on government land which is a public facility for the benefit of the community is a vanity act and the act is illegal, there are two strict sanctions in fiqh, first, the government has the right to strictly prohibit someone who builds on the land of public facilities. Second, anyone, especially the government, has the right to demolish the building